The effects of transitional care on quality of life in patients - Rezapour-Nasrabad, Rafat (Opción)
The purpose of this study was to compare the effects of transitional care before and after intervention on quality of life in patients with chronic heart failure via an interventional method with the help of Minnesota Living with Heart Failure Questionnaire. As a result, the patients’ quality of life after the intervention is significantly higher than that before intervention in different terms namely physical, emotional, and socioeconomic. In conclusion, measuring changes made to patient’s health over time, for example, symptoms of illness, physical functioning, and quality of life in patients, represent the effect of the model on patient’s recuperation.